Formulas with verba dicendi controlling the language behaviour of the recipient in the Saxon Mirror by Paweł Szczerbic (16th century) - Jurewicz-Nowak, Magdalena (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The paper is devoted to language behaviour functionally conditioned. The material base is Speculum Saxonum or Práwo Sáskie y Magdeburskie by Paweł Szczerbica from the 16th century. The aim of the paper is to explain to what extent this document could have influenced as a pattern of communication within the Polish national community determined by law. The analysis is integrated into the current of sociolinguistic and pragmatic research. Its subject is verba dicendi formulas, which impose certain linguistic behaviour on participants in court proceedings. Introducing the language behaviour pattern the sender signals a formula using verbal verbs, e.g.: request, ask, answer, condemn. The conducted research shows that the pattern includes the social component of the act (function, sex, the rank of the person with respect to each other) and the physical component (number of participants in the act of speech, sequence of activities, properties of space in which communication occurs). This is a multi-faceted message implemented with several codes: verbal and kinesic. In addition, the recipient receives information about the symbolic forms of behaviour that guarantee the fortune of the act.